Foliar gas exchange, morphology, and cannabinoid contents of three hemp varieties in southwest Texas - John Sunoj V. S.; Xuejun Dong; Madhumita V. Joshi; Russell W. Jessup; Daniel I. Leskovar; David D. Baltensperger (Agrosystems, Geosciences & Environment)
Abstract In the United States, a high level (≥0.3%) of the intoxicating Δ‐9‐tetrahydrocannabinol (THC) threatens farm‐scale production of hemp (Cannabis sativa L. ssp. sativa), but the linkage between THC and major physio‐morphological traits of hemp is not well known. This study aims to characterize the variations in physiological and/or morphological parameters and cannabinoid contents of three hemp varieties, that is, Berry Blossom, Painted Lady, and Skipper. Diurnal foliar gas exchange, chlorophyll fluorescence, water potential, and canopy temperature were measured on five clear days in the 2022 growing season, and cannabinoids were measured at peak flowering using high‐performance liquid chromatography. Allometric equations were developed to use easily measured biomass or morphological variables to predict variables that are more difficult to measure. The diurnal foliar gas exchange of the three hemp varieties was largely unaffected by the high temperatures of southwest Texas, with Berry Blossom and Skipper showing the highest and lowest photosynthesis, respectively, and Painted Lady having the most efficient stomatal control of gas exchange. Although the rooting depth of Berry Blossom was shallower than that of the two other varieties, there was no evidence showing the effect of rooting habit on the physiology of the studied hemp varieties, which was presumably due to the lack of water stress in our experiment. Nor were there significant differences in the cannabinoid contents in relation to environmental and varietal responses, as the measured THC contents of all three varieties were under 0.3%. Overall, the three hemp varieties showed different behavior strategies in southwest Texas.